2022
DOI: 10.1002/mabi.202200090
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Water‐Soluble Cyclodextrin‐Based Polymers in Biomedical Applications: How Far Are We?

Abstract: Cyclodextrin-based polymers can be prepared starting from the naturally occurring monomers following green and low-cost procedures. They can be selectively derivatized pre-or post-polymerization allowing to fine-tune functionalities of ad hoc customized polymers. Preparation nowadays has reached the 100 g scale thanks also to the interest of industries in these extremely versatile compounds. During the last 15 years, these macromolecules have been the object of intense investigations in view of possible biomed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 150 publications
0
13
0
Order By: Relevance
“…22,23 Moreover, the manufacture requires a very low number of reagents with accessible costs keeping the synthesis cheap and the natural CyD starting materials are enzymatically produced. [24][25][26] The preparation of these polymeric compounds is a standardized process at laboratory-scale and batch-to-batch reproducibility as well as the in-depth characterization of these derivatives has been largely achieved. Some EPI crosslinked CyD polymers are nowadays commercially available as ne chemicals produced on 100 g scale.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…22,23 Moreover, the manufacture requires a very low number of reagents with accessible costs keeping the synthesis cheap and the natural CyD starting materials are enzymatically produced. [24][25][26] The preparation of these polymeric compounds is a standardized process at laboratory-scale and batch-to-batch reproducibility as well as the in-depth characterization of these derivatives has been largely achieved. Some EPI crosslinked CyD polymers are nowadays commercially available as ne chemicals produced on 100 g scale.…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, they are able to associate drugs much more efficiently than the monomeric CyDs, known excipients, and to incorporate two or more therapeutics simultaneously assembling in NPs. [26][27][28] The CyD polymer NPs can help overcome standard drug shortcomings such as low solubility and poor stability in pharmaceutical vehicles for drug administration. 29,30 Last but not least, they have also far superior solubility in water; bCyD can reach a maximum concentration of 0.01 M in water while the epichlorohydrin-crosslinked bCyD polymer (pbCyD) can bring the bCyD content up to 0.1 M. 31,32 Overall, these features make CyD polymers very attractive for the development of new drug delivery systems.…”
Section: Introductionmentioning
confidence: 99%
“…The most common host unit attached to a polymer is represented by cyclodextrins (CDs). Functional polymers based on cyclodextrin have been DOI: 10.1002/macp.202200444 designed and studied reported in time highlighting the enhancement of encapsulation and release ability, the improvement of mechanical characteristics, biodegradability, [1][2][3] Alg is an anionic polysaccharide that is generally used in biomedical and pharmaceutical applications due to its biodegradability, nontoxicity, biocompatibility, low immunogenicity, etc. [4][5][6][7] A number of studies reported on the synthesis of Alg modified with cyclodextrin units.…”
Section: Introductionmentioning
confidence: 99%
“…[27] Also, polymeric networks based on CyDs have shown interesting ability to catalyse in heterogeneous phase the hydrogenation of aromatic molecules [28] or the formation of metal-nanoparticles, [29] but homogeneous phase catalysis involving CyD polymers as reaction matrix has not been reported so far. These biocompatible polymers [30] are fascinating materials mainly for three factors: [20,30] i) straightforward synthesis in water (polycondensation of CyD monomers with a crosslinking agent, i. e., epichlorohydrin, BCDPS, Figure 1C); ii) improved aqueous solubility ([βCyD] as monomers reaches � 0.01 M, while [βCyD] is � 0.10 M dissolving BCDPS of MW � 50 kDa with βCyD content � 70 % w/w); iii) ability to encapsulate more guests simultaneously.…”
Section: Introductionmentioning
confidence: 99%